Study of hardness on the stainless steel in various cooling medium / Muhammad Fikri Harun Anuar - Harun Anuar, Muhammad Fikri (2022)
Due to its superior mechanical qualities when compared to other materials, stainless steel is utilised extensively in various fields; thus, its properties must be improved to keep up with modern trends. Designing high-durability and reliable constructions can increase the safety factor for items, ensuring the users' security. This research was done to find out how heat treatment affected the microstructure and hardness of heat-treated stainless steel. Stainless steel samples will be heated under varied temperature and soaking time conditions.